Analisis Kausalitas Antara Variabel Jumlah Industri, Investasi, Dan Upah Minimum Provinsi Terhadap Penyerapan Tenaga Kerja Provinsi Jawa Timur - I Gede Ardiyana; Niniek Imaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The East Java Province is one of the second-largest populations on the Island of Java, however the labor absorption in East Java tended to be lower by fifth place on the Island of Java. The aim of this research was to see how causality is related between the amount of industry, investment, and minimum wages of province on the labor absorption in East Java Province. The method used in this research is Vector Autoregression (VAR) with Granger’s causality test and Vector Error Correction Model test, also using quantitative approach. The data used in this research is data time series from 2011 until 2021 was obtained from the Indonesia and East Java Province statistical center, investment and joint service one door of East Java Province, and also from another literature study. The result was that the amount of industry had two-way causality, while the minimum wage of the province had only one directional causality and both had negative impact on the labor absorption of the East Java Province. Meanwhile, investment had positive impactand had only one directional causality on the labor absorption of the East Java Province. Keywords : Investment; Industrial Amount; Absorption of Labor; Minimum Wage